1997
DOI: 10.2752/089279397787000987
|View full text |Cite
|
Sign up to set email alerts
|

Dog-Human Relationship Affects Problem Solving Behavior in the Dog

Abstract: In this paper we present evidence that simple problem solving in the dog is strongly influenced by the relationship with the owner. Twenty-eight dog-owner pairs were observed in a novel situation and when performing a simple problem-solving task. Dogs were categorized according to their relationship with the owners ("companionship" or "working relationship"). In addition to the behavioral analysis of the dogs, the anthropomorphic attitudes of the owners were assessed by a questionnaire. Factor analysis showed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
96
2
4

Year Published

2001
2001
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(107 citation statements)
references
References 34 publications
5
96
2
4
Order By: Relevance
“…Accordingly, it can be speculated that the restricted manifestation of dogs' reasoning abilities is not due to the effect of domestication in the reduction of problemsolving abilities (Frank 1980) but it is being masked by bias in following social cues. This would be in line with the dependency argument made by Topál et al (1997).…”
Section: U N C O R R E C T E D P R O O Fsupporting
confidence: 75%
“…Accordingly, it can be speculated that the restricted manifestation of dogs' reasoning abilities is not due to the effect of domestication in the reduction of problemsolving abilities (Frank 1980) but it is being masked by bias in following social cues. This would be in line with the dependency argument made by Topál et al (1997).…”
Section: U N C O R R E C T E D P R O O Fsupporting
confidence: 75%
“…The short duration of the dogs' concentration on the food thus does not seem to reflect that the animals are disorganised but rather that they lost interest. Further, Topál et al (1997) found that dogs' poor problemsolving performance was less dependent on their cognitive abilities than on their dependent relationship with the owner. We could assume that the dogs' relationship with the owner masked any association between the questionnaire items of Trainability and their performance in the test.…”
Section: Association Between Owners' Subjective Rating and Behaviour mentioning
confidence: 99%
“…Further on, instead of reporting only their success, two behavioural aspects were examined that had already been documented to be important in dog-human communication. These are the dogs' sensitivity to human gestural cues when locating hidden food (Soproni et al 2001), and their tendency to look at humans in problem situations (Topál et al 1997;Miklósi et al 2000;Pongrácz et al 2001;Miklósi et al 2003;Gácsi et al 2005). Accordingly, dogs and wolves were compared in both of these aspects.…”
Section: Introductionmentioning
confidence: 99%